Sound transmission through slits and circular apertures - A. TROCHIDS; G. PAPANIKOLAOU (Archives of Acoustics)
In this paper the sound transmission through slits and circular apertures is examined. Approximate theoretical expressions for the transmission loss are derived using simple energy balance considerations. Both resonant and nonresonant transmissions are taken into account. Theoretical values of the transmission loss are compared with measurements.